2009
DOI: 10.1088/0022-3727/42/21/215406
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of highly doped Er3+ : GGG and Er3+/Pr3+ : GGG crystals

Abstract: Heavily Er3+-doped and Er3+/Pr3+ co-doped Gd3Ga5O12 (abbreviated as Er : GGG and Er,Pr : GGG, respectively) laser crystals were synthesized by the Czochralski method. The synthesized laser crystals were characterized by absorption, up-conversion fluorescence, near-infrared (NIR) and mid-infrared (Mid-IR) fluorescence, and luminescence decay measurements. The optical parameters related to absorption and emission cross-sections and fluorescence lifetimes were evaluated and compared. It was found that the up-conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 19 publications
1
63
0
3
Order By: Relevance
“…The growth procedure was similar to that of Er:GGG described in our previous publication [29]. The concentration of praseodymium ions in the crystal was measured to be 0.268 wt% by the inductively coupled plasma-atomic emission spectrometry (ICP-AES) method and the corresponding Pr 3+ concentration is 8.12 × 10 19 ions/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth procedure was similar to that of Er:GGG described in our previous publication [29]. The concentration of praseodymium ions in the crystal was measured to be 0.268 wt% by the inductively coupled plasma-atomic emission spectrometry (ICP-AES) method and the corresponding Pr 3+ concentration is 8.12 × 10 19 ions/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…5, the luminescence decay curve of the 1 D 2 → 3 H 4 transition at the wavelength of 608 nm excited by 590 nm pumping is not singly exponential, but could be described as two exponentials, among which the lifetime of 1 and 2 components are estimated to be 63.5 and 144.6 s, respectively. And the lifetime the 1 D 2 manifold is estimated to be 118.4 s by using = (B 1 1 2 + B 2 2 2 )/(B 1 1 + B 2 2 ) [29], which is much longer than that of 3 P 0 level. The experimental lifetime value of the 1 D 2 level can be compared to that of 1 mol%Pr:GGG nanocrystalline: 110s [25], 0.5% Pr 3+ :YAG: 110s [45] and of 1% Pr 3+ :YAP: 28s [43].…”
Section: Fluorescence Lifetimes and Quantum Efficiencymentioning
confidence: 99%
“…It is noticed that the fluorescence lifetime of 4 I 11/2 state (0.629 ms) is much shorter than that of 4 I 13/2 state (6.067 ms) in Er:SGGM crystals. As we know, the shorter lifetime of laser upper level 4 I 11/2 than lower level 4 I 13/2 will make the accumulated population in the 4 I 11/2 levels not relax rapidly enough to maintain the required population inversion, and then cause the $ 3.0 mm lasing transition to selfterminate [1,4].…”
Section: Fluorescence Decay Curves and Energy Transfer Efficienciesmentioning
confidence: 99%
“…This is primarily due to the strong absorption by water around this wavelength, making erbium doped lasers suitable for use in medical applications, hazardous chemical detection, remote atmospheric sensing and pollution monitoring etc. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…But, when Er 3+ ion is heavily doped, the cross-relaxation plays a dominant role and the fluorescence kinetics changes obviously. Thus, it is suggested that high Er 3+ concentration can increase the population of 4 I 11/2 and depopulate 4 I 13/2 level and so benefits 2.7 lm emission [3][4][5].…”
Section: Introductionmentioning
confidence: 99%